New information on the distribution of scorpions of the genus Anomalobuthusin Kazakhstan - Fedorov, А.А.; Yeszhanov, A.B. (Fundamental and Experimental Biology, 2022)
Arachnids (Arachnida) are an extensive class of arthropod invertebrates, numbering 114 thousand species, while the most numerous in terms of the number of taxa are spiders (Aranei) and ticks (Acari). Arachnids are found in all continents of the globe and are the second largest group of taxa after insects. This group of animals is of great importance in the functioning of ecosystems, since arachnids play an important role in food chains, and are also vectors of a wide range of infections, especially dangerous ones. Finally, representatives of some orders of these arthropods are valuable venom producers. Nevertheless, this group of invertebrates has been studied unevenly, and information on various species of arachnids is often fragmentary. For example, it was previously believed that only one monotypic genus with a single species lives on the territory of Kazakhstan — Anomalobuthus rickmersiKraepelin, 1900, which was included in the Red Book of the country. However, according to the latest data, it became known about the description of3 more species of this genus for Kazakhstan. At the same time, the available information on the newly described species refers only to a few finds in Kazakhstan, while information on the range of the genus Anomalobuthusremains scarce and fragmentary. This article is a report on the discovery of a previously unknown settlement of a scorpion of the genus Anomalobuthus (presumably A.lowei Teruel 2018) on the right bank of the Ile River in Southeastern Kazakhstan, provides information about the area where the scorpion was found, and its density.